1979
DOI: 10.1111/j.1755-3768.1979.tb06666.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ultrastructure of the Normal Conjunctival Epithelium of the Guinea Pig

Abstract: The ultrastructure of the superficial cell layer of the perilimbal zone of the guinea pig conjunctival epithelium as seen in transmission and scanning electron micrographs is described. The major interest is focused on the apparatus of vesicles, vacuoles and cysts and their possible significance in connexion with transport functions and autophagocytic processes. The importance of the cell surface components and the role of the microfilaments in phagocytosis are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
4
17
0
Order By: Relevance
“…Because of its histological appearance, the conjunctiva was divided into four zones. Several authors graded the conjunctiva of guinea pigs, 13–18 rats, 19 and mice 20 in a different way to ours; however, in the study by Gasser et al. , 9 the zoning system in guinea pigs was reported similar to ours.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Because of its histological appearance, the conjunctiva was divided into four zones. Several authors graded the conjunctiva of guinea pigs, 13–18 rats, 19 and mice 20 in a different way to ours; however, in the study by Gasser et al. , 9 the zoning system in guinea pigs was reported similar to ours.…”
Section: Discussionsupporting
confidence: 62%
“…Because of its histological appearance, the conjunctiva was divided into four zones. Several authors graded the conjunctiva of guinea pigs, [13][14][15][16][17][18] rats, 19 and mice 20 in a different way to ours; however, in the study by Gasser et al, 9 the zoning system in guinea pigs was reported similar to ours. A limbal zone, defined by the presence of melanocytes within the basal layer of the epithelium, has been described in guinea pigs.…”
Section: Conjunctiva and Goblet Cellssupporting
confidence: 61%
See 3 more Smart Citations